Efektivitas Bahan Ajar Persamaan Differensial Berbasis Problem Based Learning pada Pokok Bahasan Persamaan Diferensial - Rofiroh Rofiroh; Yani Setiani; Linda (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to test the effectiveness of Differential Equations (PD) teaching materials based on Problem Based Learning (PBL). The main component of teaching materials is a medium to bridge the curriculum with students' learning experiences. The current PD lecture conditions are still dominated by 56% of lecture methods. This results in students having difficulty in understanding applicable concepts and mastering mathematical modeling skills. The research method used is quantitative with a quasi-experimental approach tested on 25 third-semester PD course students. The effectiveness of teaching materials was tested using N-gain analysis and Wilcoxon Signed Rank Test. The results of the study showed a significant increase in the average value from the pre-test (17.24) to the post-test (75.36). The average N-gain of 0.81 is categorized as high. The results of the Wilcoxon Test showed an Asymp.Sig (2-tailed) value of 0.00 <0.05. This means that there is a significant difference between the values ??before and after the use of PBL teaching materials. This is evident from the fact that 92% of students agreed that PBL learning materials can improve their thinking skills in solving PD problems.